BIM Maintenance System with IoT Integration: Enhancing Building Performance and Facility Management - Ahmed Ehab; Mazkour A. Mahdi; Arfa El-Helloty (Salehan Institute of Higher Education, 2024)
The rapid growth of technology worldwide in different ways drives the construction sector to take the same path. Smart cities, Digital Twins, Building Information Modeling (BIM), and the Internet of Things (IoT) are the trends in this way today. Also, integrating Building Information Modeling (BIM) and Internet of Things (IoT) technologies has revolutionized how buildings are designed, constructed, maintained, and managed. On the other hand, the complexity, high cost, need for expertise, and other things make the maintenance process and facility management by human inspections, commercial software, and different tools not suitable for the growth of the technology. This paper presents a proposal for a workflow of integration between BIM, and an algorithm of Maintenance System with IoT and highlights its potential to enhance building performance and facility management. The paper explores this innovative system's underlying principles, benefits, challenges, and implementation strategies. Furthermore, it discusses the implications of BIM, and the proposed algorithm of Maintenance System with IoT integration on various stakeholders, including building owners, facility managers, and occupants by using a case study. The findings collected by a questionnaire for some experts emphasize the importance of adopting this integrated approach to optimize building operations, improve maintenance practices, and create sustainable and intelligent built environments. Doi: 10.28991/CEJ-2024-010-06-015 Full Text: PDF